Peptides: Minimal drug surrogates to interrogate and interfere with protein function - Cruz-Migoni, A; Fuentes-Fernandez, N; Rabbitts, T (2013)
The interactome in normal and disease cells is a key area for study and therapeutic targeting, yet few molecules have been developed that can interfere with protein-protein interactions within cells. A variety of options are being examined to target protein-protein interfaces in simple and in multi protein complexes. The work of Hamilton and colleagues has developed approaches to the synthesis of proteomimetics for this purpose and thus recognized novel scaffolds can be critical reagents to protein targets. In this short report, we have outlined two of our own molecular biology approaches to specific peptide isolation targeting protein interfaces for peptide design, with the goal being eventual therapeutic intervention. This journal is © The Royal Society of Chemistry.